(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Inclusive education aims to provide equal access for all students, including those with emotional and behavioral disorders (EBD). However, its implementation still faces challenges, especially in creating a supportive learning environment. Teachers play an important role by implementing appropriate learning strategies. This research uses the literature study method to analyze the role of teachers in understanding students with GEP, strategies used, challenges faced, and solutions that can be applied. The data sources used include scientific journals as the main reference. The research process includes problem identification, literature search and selection, content analysis, and conclusion formulation based on the findings of the various references reviewed. The results show that teacher training, collaboration with experts, and supportive policies are needed for the success of inclusive education for students with GEP.